PREVALENCE OF MYOFASCIAL DYSFUNCTIONS IN BREAST CANCER SURVIVORS (International Journal of Physiotherapy, 2019)
Background: After breast cancer treatment, many complications are seen in breast cancer survivors (BCS). In that musculoskeletal dysfunctions are common. These dysfunctions are one of the common sources of pain and disability. A recent study states that extreme pain after breast cancer treatment is often. Severe pain can be a source of a lot of limitations and psychological distress. Before the time assessment and rehabilitation can be inserted to reduce pain level, improve strength and mobility which will be helpful in minimize restrictions in daily living and improve quality of life (QOL). The objectives of the study were as follows: To determine the prevalence of myofascial dysfunctions in BCS. To study the association of myofascial dysfunctions and demographic variables in BCS.Methods: A total of 74 females who underwent breast cancer surgeries along with chemotherapy or radiotherapy or hormone therapy, were included based on inclusion criteria. Subjects were assessed for pectoralis tightness, postmastectomy pain syndrome (PMPS), rotator cuff diseases, adhesive capsulitis, lymphedema and axillary web syndrome (AWS) by using Visual Analogue Scale (VAS), Musculoskeletal Assessment and pectoral tightness test.Results: Primary outcomes used for the result were Musculoskeletal Assessment, Visual Analogue Scale, posture Assessment, pectoral tightness test. The most common type of myofascial dysfunctions was Pectoral tightness (p=0.1344), post-mastectomy pain syndrome (p=0.0116), rotator cuff disease (p= 0.1344), adhesive capsulitis (p= 0.9388) and axillary web syndrome (p= 0.9193) and the result was extremely significant.Conclusion: The major postoperative myofascial dysfunctions above the age of 50 years are pectoralis tightness, rotator cuff, and then by adhesive capsulitis and that of below 50 years was adhesive capsulitis followed by lymphedema and by rotator cuff disease.